Use of E-Resources as an Effective Means of Organizing an Educational Quest in An Institution of Higher Education - Horokhova, Tetiana; Zarudnia , Olha (Educological discourse, 2023)
The article explores the possibilities of using e-resources for organizing an educational quest in higher education institutions. Presented different approaches to defining the essence of the concepts of «quest», «online quest», «web quest» (as a technique, means, method, approach, learning technology) in the scientific, pedagogical and methodological literature. The article defines online quest as a game-based pedagogical technology and reveals its role in the formation of students' key, professional, linguistic and communicative competencies, acquisition of skills of independent research and improvement of group interaction skills. The authors have identified and characterized the main stages of implementing an online quest, as well as revealed the principles of selecting educational resources and identified aspects of creating tasks. The structure of an online educational quest using digital tools is described. Main attention is paid to the group work of the participating teams on the Learningapps online platform and the Padlet online board, especially their potential during the interactive online quest «Language Marathon» at Borys Grinchenko Kyiv University is substantiated. Showed examples of linguistic, literary and creative tasks are presented, evaluation criteria are highlighted and the principles of interpretation of the results are formulated. The role of the online quest in the formation of students' cultural and linguistic personality is substantiated and the advantages of this approach are identified, in particular, increasing students' motivation and acquiring a number of general professional and linguistic competencies. The relevance and expediency of organizing an educational quest using electronic resources in higher education institutions are empirically confirmed.